2018
DOI: 10.51983/ajeat-2018.7.2.948
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled CNT Reinforcement to Thermal Spray Coatings

Abstract: Thermal spraying coating techniques have emerged as very effective surface protection technology to apply protective coatings for corrosion and wear resistance applications. These coatings have gained more importance in recent past. Advances in powder and wire production have resulted in development of various types of surface coatings with excellent wear and corrosion resistance properties. Because of excellent mechanical, thermal and electrical properties of Carbon Nanotubes, CNTs reinforced composite coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Kaushal et al [13] used detonation gun spray method to deposit Ni-20Cr onto ASTM A213 TP347H boiler steel and results revealed that coating had potential to lower the high temperature corrosion. Goyal et al [14] outlined the role of corrosion and effect of coatings on the properties of various engineering materials and concluded that Ti-Al-N and Cr-Al-N exhibit greater plastic hardness which contributes to its better wear performance. But Cr-Al-N proved to have exceptionally high wear and oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Kaushal et al [13] used detonation gun spray method to deposit Ni-20Cr onto ASTM A213 TP347H boiler steel and results revealed that coating had potential to lower the high temperature corrosion. Goyal et al [14] outlined the role of corrosion and effect of coatings on the properties of various engineering materials and concluded that Ti-Al-N and Cr-Al-N exhibit greater plastic hardness which contributes to its better wear performance. But Cr-Al-N proved to have exceptionally high wear and oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%